2018
DOI: 10.1186/s13019-018-0785-7
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial insufficiency is related to reduced subunit 4 content of cytochrome c oxidase

Abstract: BackgroundTreatment of heart failure remains one of the most challenging task for intensive care medicine, cardiology and cardiac surgery. New options and better indicators are always required. Understanding the basic mechanisms underlying heart failure promote the development of adjusted therapy e.g. assist devices and monitoring of recovery. If cardiac failure is related to compromised cellular respiration of the heart, remains unclear. Myocardial respiration depends on Cytochrome c- Oxidase (CytOx) activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 43 publications
(61 reference statements)
2
16
0
Order By: Relevance
“…Ischemic stress induces Cox3 upregulation, Cox1 downregulation, impaired Cox oxidative activity, and apoptosis in monkey models of MI 37 . In human myocardial insufficiency and dilated cardiomyopathy, decreased Cox4 results in impaired Cox oxidative activity 38 . Thus, several studies have reported associations between Cox5a and hypoxic environments and between other Cox subunits and heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic stress induces Cox3 upregulation, Cox1 downregulation, impaired Cox oxidative activity, and apoptosis in monkey models of MI 37 . In human myocardial insufficiency and dilated cardiomyopathy, decreased Cox4 results in impaired Cox oxidative activity 38 . Thus, several studies have reported associations between Cox5a and hypoxic environments and between other Cox subunits and heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…In heart failure, higher enzymatic activity with maintained oxygen consumption contributes to the physiopathology of myocardial insufficiency and appears to be an indicator of oxidative stress [ 162 ]. In 2021, Ortega-Gomez et al [ 51 ] developed a plasmonic tip biosensor for the detection of reduced cytochrome c, which is a multifunctional enzyme with a crucial role in electron transfer in the mitochondrial transport chain.…”
Section: Biosensing Applicationsmentioning
confidence: 99%
“…Cytochrome C is a key electron carrier for mitochondrial electron transport to cytochrome C oxidase, and its release from the mitochondria into the cellular cytoplasm triggers cellular apoptosis. It has also been found that lack of cytochrome C oxidase activity leads to myocardial insufficiency and dysfunction via reduction in mitochondrial respiration 20 . Any specific mutations in mtDNAs encoding OXPHOS, rRNAs or tRNAs required for mitochondrial protein synthesis are also involved in cardiovascular diseases 21,22 .…”
Section: Mitochondrial Disturbance and Cardiovascular Diseasementioning
confidence: 99%
“…It has also been found that lack of cytochrome C oxidase activity leads to myocardial insufficiency and dysfunction via reduction in mitochondrial respiration. 20 Any specific mutations in mtDNAs encoding OXPHOS, rRNAs or tRNAs required for mitochondrial protein synthesis are also involved in cardiovascular diseases. 21,22 Mitochondrial dysfunctions because of other factors, including mitochondrial structural disorganization, enlargement or through changes of membrane potential can trigger the mitochondrial degradation mechanism.…”
Section: Disturbance and Cardiovascular Diseasementioning
confidence: 99%